The Effects of Vestibular Stimulation and Fatigue on Postural Control in Classical Ballet Dancers. Issue 2 (June 2014) - Hopper, Diana M.; Grisbrook, Tiffany L.; Newnham, Prudence J.; Edwards, Dylan J.
This study aimed to investigate the effects of ballet-specific vestibular stimulation and fatigue on static postural control in ballet dancers and to establish whether these effects differ across varying levels of ballet training. Dancers were divided into three groups: professional, pre-professional, and recreational. Static postural control of 23 dancers was measured on a force platform at baseline and then immediately, 30 seconds, and 60 seconds after vestibular stimulation (pirouettes) and induction of fatigue (repetitive jumps). The professional dancers' balance was unaffected by both the vestibular stimulation and the fatigue task. The pre-professional and recreational dancers' static sway increased following both perturbations. It is concluded that professional dancers are able to compensate for vestibular and fatiguing perturbations due to a higher level of skill-specific motor training.